"Stylistic Deception" In the Abbasid poetry, its impact on the receiver (Journal of the College of Basic Education, 2022)
This study sought to reveal the methods of poets - some of whom are poets in the Abbasid era - in the misguided sense, and covered with stylistic graphic techniques resorted to by the poet through the language play in the (textile) from which the text is composed. That is, to act in the grammatical, morphological, and semantic relations, which enables it to produce its whole sentence, expressions, and expressions in its aesthetic form, to stimulate the recipient, and to provoke him to participate in the production of the literary text and to intensify its significance. These playgrounds and catacombs are different new images that are revealed by breaking a familiar rule that has a great impact on the psyche of the recipient by involving him in highlighting some of the elements of the beauty of the text and drawing attention to it and analyzing it aesthetically reveals deep indications hidden under the cloak of the apparent words.